Factors associated with the quality of health services for hypertension patients at adow community health center, Central Pinolosian Sub District South Bolaang Mongondow Regency - Kolibu, Febi K.; Kawatu, Paul; Tucunan, Ardiansah (International Journal Of Community Medicine And Public Health, 2022)
Background: The community’s need for health services encourages health care facilities to always provide quality services. The implementation of health service quality assurance will not only have an impact on the organization, but also satisfaction for existing resources within the organization because of patient satisfaction. The purpose of this study was to determine the relationship between the dimensions of the quality of health services with the satisfaction of hypertension patients at the Adow public health center, central Pinolosian Sub District, South Bolaang Mongondow Regency. Methods: This study is a quantitative study with a cross-sectional design. The study population consisted of hypertensive patients at Adow health center with a total sample of 100 patients who were taken using the purposive sampling technique. Results: Univariate analysis on the quality of health services found 67% of respondents stated that the dimensions of tangible were good, 50% of patients stated that the dimensions of reliability were good, 88% of patients stated that responsiveness was good, 72% of patients stated that the dimensions of assurance were good and 92% The patient stated that the empathy dimension was good. The results of the bivariate analysis proved the correlation between the dimensions of physical evidence-satisfaction of hypertensive patients (p=0.000), the dimensions of reliability-satisfaction of hypertensive patients (p=0.000), dimensions of responsiveness-patient satisfaction (p value 0.000), assurance-patient satisfaction (p=0.002) and empathy-patient satisfaction (p=0.017) Conclusions: The quality of health services for hypertensive patients at the Adow community health center based on an assessment of the dimensions of tangible, reliability, responsiveness, assurance, and empathy is included in the good category. There is 53% of patients expressed their satisfaction with the services provided by the Adow community health center. In addition, this study has proven that there is a relationship between physical evidence, reliability, responsiveness, assurance, and empathy with the satisfaction of hypertensive patients at the Adow community health center.